If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -18 = 2(x + -2) Combine like terms: 26 + -18 = 8 8 = 2(x + -2) Reorder the terms: 8 = 2(-2 + x) 8 = (-2 * 2 + x * 2) 8 = (-4 + 2x) Solving 8 = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + -2x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + -2x = -4 + 0 8 + -2x = -4 Add '-8' to each side of the equation. 8 + -8 + -2x = -4 + -8 Combine like terms: 8 + -8 = 0 0 + -2x = -4 + -8 -2x = -4 + -8 Combine like terms: -4 + -8 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| 540-8P=120+6P | | 4(8a+-8)= | | 8z=12 | | 2x-sin(0.5x)=0 | | 7x-12=15-4x | | 8x-(x-4)=7x | | =6P+540 | | y^2-2y-35= | | 4t-2= | | x+18+4x=-10-4x-17 | | t^2-8t=19 | | 58=-8(8m+5)-3-m+8 | | -7x+3y=38 | | 2x-(x+2)=-4 | | 19-x=14 | | 2(4-7)= | | 9t-6t+t-2= | | -109+x=34+12x | | -6-13=5x+18-4x | | 78=3(x)+18 | | 12c-15=11 | | 13*2+3= | | x=2y+2z+24 | | (3-u)(2u+9)=0 | | 8-5+3-4= | | Y=3x^3-2x^2-12x+8 | | 6x+25=74 | | Y=3x^2-2x^2-12x+8 | | (2v-7)(1-v)=0 | | 22y-198x=110 | | 16p=208whatisp | | 8(x+1)+4(x+1)=6x-6 |